A reduced form of shakedown kinematic theorem - Chinh, Pham Duc (Vietnam Journal of Mechanics, 2002)
A reduced form of the shakedown kinematic theorem without time integrals is deduced for Tresca material, which is equivalent to the original one when the principal directions of plastic deformations everywhere in a structure remain unchanged during loading cycles.